Les « pratiquants » de l’Agriparc : mise en perspective des valeurs environnementales liées au milieu de vie - Hélène Houdayer (VertigO)
The city of Montepllier is experiencing a positive migratory dynamics exerting a land pressure resulting in a susburban sprawl, and on an increase attendance of green spaces. For this study, we started with the point of view of developers of one of the two Agri(cultural)parks in Montpellier to think about the socialization process of a space as living environment. For this purpose, we conducted an investigation among professional users (practitioners) of this park. By presenting projects which combine urban and agricultural functions, generally observed in periurban areas, they are clearly involved in the sustainable development approach. Our investigation illustrate how it is possible for Agripark's users to play a role in the conservation of an ecosystem frequently visit by the inhabitants, while conceding a central position to farmers. The whole substantially participate to the socialization process. Considering proposed environmental values by practitioners, we also demonstrate the Agripark project attractiveness. Indeed the Agripark operates the links between nature and culture by playing on users’ emotions, by the organic nature of implemented crops, and by giving a special attention to the biodiversity aspect of the project.